Efeitos do hipertireoidismo materno na histomorfometria dentária e periodontal da prole nos períodos pré- e pós-natal em modelo murino - Douglas Marinho Abreu (2022)
Ten pregnant Wistar rats were used, five of which were induced to hyperthyroidism throughout pregnancy and lactation, and five rats were maintained in a euthyroid state (control). Hyperthyroidism was induced by the daily administration of L-thyroxine through an orogastric tube, at a dose of 50 µg/animal/day, throughout the entire period of pregnancy and lactation. Control females received a placebo in the same dosage schedule. Three days after birth, 3 newborns/mothers were selected and the rest of the pups were breastfed by the control and hyperthyroid mothers until weaning at 21 days. On the day of weaning, 3 pups/mothers were randomly selected. Four experimental groups were totaled 1) neonates born to control mothers; 2) newborns born to hyperthyroid mothers; 3) weanling offspring from control mothers; 4) weaning puppies from hyperthyroid mothers. Maternal hyperthyroidism was confirmed by the measurement of free T4 in the mother's plasma and the influence of maternal hormones on the offspring was confirmed by thyroid histomorphometry. The thickness of the ameloblasts, enamel, dentin, predentin and odontoblasts layers in the crown region and the thickness of the dentin, predentin, and odontoblasts layers in the region of the newborns were measured in the molar teeth of the newborns. In the pups' teeth at weaning, the thickness of the dentin, predentin, and odontoblast layers was evaluated, as well as the thickness of the periodontal ligament and the morphological evaluation of the alveolar bone. The design was completely randomized and for each variable, the mean and standard deviation were determined. Data were submitted to the Student t-test for comparison of means. Differences were considered significant if p<0.05. Free T4 dosage was higher in treated mother rats and the height of the thyroid follicular epithelium was lower in all offspring of hyperthyroid mothers. The molars of control neonates and hyperthyroid mothers presented a morphology consistent with normality, with no differences between groups. There was also no significant difference in the thickness of the layers of the crown and root regions between the groups. At weaning, the offspring of hyperthyroid rats showed morphological characteristics like the control group, however, the thickness of the odontoblast and predentin layers was significantly smaller, unlike the periodontal ligament, which was significantly thicker when compared to the control group. The alveolar bone showed similar morphological characteristics between groups. It is concluded that the effects of maternal hyperthyroidism on the dental and periodontal development of the offspring of rats are morphologically manifested only in the postnatal period, that is, at weaning, when there is a reduction in the thickness of the odontoblast and predentin layers and an increase in the thickness of the periodontal ligament. Keywords: odontogenesis, thyroid dysfunctions, rat, morphometry, periodontal